Second Order Duality in Mathematical Programming with Support Functions - Husain, I.; Masoodi, M. (Journal of Informatics and Mathematical Sciences, 2009)
Wolfe and Mond-Weir type second order dual programs are formulated for a non-linear programming problem in which the objective as well as each of constraint functions contain a term of a support function. Special cases are also deduced from our results.